Measurements of the mechanical response of unidirectional 3D-printed PLA. (5th June 2017) - Song, Y.; Li, Y.; Song, W.; Yee, K.; Lee, K.-Y.; Tagarielli, V.L.
Abstract: Fully dense PLA blocks were manufactured by 3D-printing, depositing a polymer filament in a single direction via the fusion deposition method (FDM). Specimens were cut from printed blocks using conventional machining and were used to perform tension, compression and fracture experiments along different material directions. The elasto-plastic material response was found to be orthotropic and characterised by a strong tension-compression asymmetry; the material was tougher when loaded in the extrusion direction than in the transverse direction. The response of the unidirectional, 3D-printed material was compared to that of homogeneous injection-moulded PLA, showing that manufacturing by 3D-printing improves toughness; the effects of an annealing thermal cycle on the molecular structure and the mechanical response of the material were assessed. Graphical abstract: Highlights: 3D-printed PLA displays an elasto-plastic, orthotropic mechanical response with a strong tension/compression asymmetry. The material is tougher when tested in the extrusion direction ( K IC = 5 MPa m ) than in the transverse direction ( K IC = 4 MPa m ). Manufacturing by 3D-printing results in higher toughness than manufacturing by injection-moulding ( K IC = 3 MPa m ). Annealing at a temperature below T g has negligible effect on crystallinity and stiffness but reduces the strength 10 to 30%.